1970
DOI: 10.1128/jb.101.2.490-504.1970
|View full text |Cite
|
Sign up to set email alerts
|

ICR-Induced Frameshift Mutations in the Histidine Operon of Salmonella

Abstract: Both the acridine half-mustard, ICR191, and the nonalkylating azaacridine derivative, ICR364-OH, induce three classes of frameshift mutations in the histidine operon of Salmonella typhimurium. (i) One class is completely stable in reversion tests and is presumed to represent deletion of one or a few critical nucleotide pairs or two nearby frameshifts. One extended deletion was found out of 11 stable mutations. (ii) Of two spontaneously reverting classes which also are considered to predominantly involve base d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1972
1972
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The lacZ and trpA mutations used were either not reverted or only slightly reverted by NG, an agent that primarily induces transitions and transversions but can induce frameshift mutations (18). However, it is still possible that transitions induced by the mutator genes resulted in the increases in frameshift reversion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lacZ and trpA mutations used were either not reverted or only slightly reverted by NG, an agent that primarily induces transitions and transversions but can induce frameshift mutations (18). However, it is still possible that transitions induced by the mutator genes resulted in the increases in frameshift reversion.…”
Section: Resultsmentioning
confidence: 99%
“…Imada et al (12) concluded from their own work and that of others that acridines predominantly induce base additions. Oeschger and Hartman (18) considered almost 50% of the ICR compoundinduced frameshift mutations in S. typhimurium to be base additions. Possibly, lacZ(ICR36), lacZ(ICR48), and lacZ(ICR75) are base additions, whereas lacZ(X84) (induced by X irradiation [171) and lacZ[36-16(-) ] (spontaneous [15]), which did not respond as strongly to the mutator genes, are base deletions.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining strains, ME1047 aralO16), ME1080 (aralO27), ME1098 (aralO36), and ME1044 (aralO15) were induced to revert by DES and ICR-191. Since neither of these mutagens appears to be entirely specific with regard to its mechanism of action (2,21), it must be tentatively concluded that these four mutants could have arisen as a consequence of either a frameshift or base pair substitution type mutation. Strains ME1044 aralO15) and ME1080 (aralO27) exhibited a "leaky" growth response on mineral-L-arabinose-leucine agar medium, suggesting that at least minimal expression of the araB gene (Lribulokinase) was occurring.…”
Section: Resultsmentioning
confidence: 99%
“…The AmeslSalmonellu typhimurium mutagenicity assay [Ames et al, 1975;Maron and Ames, 19831 is the most widely used short-term test for the detection of mutagenic and potentially carcinogenic pure compounds [Kier et al, 19861 and complex mixtures [ DeMarini, 199 1 1. In particular, tester strains containing the hisD3052 frameshift mutation have shown considerable utility in mutagenesis screening programs [Zeiger et al, 19851. The hisD3052 mutation contains a deletion of a CG base pair (bp) that was induced by the acridine nitrogen mustard ICR-354-OH [Oeschger and Hartman, 1970;Hartman et al, 19861. Previous analyses of revertants of this allele have involved 1) deduction of DNA-base changes based on the amino acid sequence of the histidinol dehydrogenase polypeptide coded by revertants of the hisD3052 allele [Isono and Yourno, 19741, 2) cloning and DNA sequencing of revertants [Fuscoe et al, 1988;O'Hara and Marnett, 19911, and 3) deduction of DNA-base changes based on colony hybridization of revertants [Cebula and Koch, 1990;Kupchella and Cebula, 19911.…”
Section: Introductionmentioning
confidence: 99%